(untitled) (Architecture Image Studies, 2023)
Historical buildings, which are important sources about the history, architectural features, social and cultural characteristics of the period in which they lived, have document value today by establishing a bridge between the past and the future. Restoration is one of the most basic areas of action of the conservation discipline, which aims to protect historical buildings and ensure cultural continuity and transfer them to future generations. Historical buildings have been designed and functioned in accordance with the requirements of the period in which they were built, and they were not used in line with the changing living standards and needs over time, and were condemned to disappear due to unconsciousness, adverse environmental conditions and neglect. Restoration procedures to be applied to these structures should be carried out by following the correct methods and by studies carried out by experts. In addition, the new functions to be added to historical buildings should be determined by adhering to the architectural, social and cultural characteristics of the building and taking into account environmental factors. These structures, which have been re-functionalized after the carefully applied restoration works, provide cultural and historical sustainability by revealing the urban identity of their period. In this context, after the restoration process, the current state of Esma Sultan mansion will be discussed. It is necessary to determine the necessary elements for the restoration processes of historical buildings, the criteria and decisions of intervention, and the characteristics of the structure before the intervention. In this direction, by considering the contemporary restoration and re-functioning works applied to the Esma Sultan mansion, it will be revealed to what extent the original qualities and features of the building are preserved, and whether the differences that are not unique to the structure brought by the new function are compatible with the character of the previous building.